Children's nutritional status - the impacts of the pandemic and their perspectives for prevention (Research, Society and Development, 2022)
Brazil currently lives in a new scenario of serious nutritional problems in childhood. In addition to malnutrition in several regions of the country, another nutritional disorder is raised: excessive weight. In addition to this context, in 2020, COVID-19 appears, making this scenario even more problematic. Thus, this study aimed to evaluate the effects of the pandemic on the nutritional health of children aged 0 to 10 years, in relation to their overweight, in the national territory. A cross-sectional, retrospective and quantitative approach was developed. Data for research were taken from official government websites, namely: SISVAN - Web (Food and Nutrition Surveillance), DATASUS and e-SUS Web, in which sociodemographic data from Brazil were analyzed and in its five socio-political regions. The variables analyzed were: gender, age group and zone of occurrence. The profile showed no statistically significant differences in the prevalence of children’s overweight in Brazil, regardless of age group, in the period between 2017 and 2021. However, there was a clear trend, although not significant, of increased prevalence of children with overweight, except in the age groups from 0 to 6 months and from 6 months to two years, which showed a stationary trend. In relation to the socio-political regions, it was possible to identify a trend of increasing weight gain for age, in all regions, being lower in the North and higher to the Southeast region. It should be noted that this trend of increasing weight gain was only significant in the southern region, where the prevalence of overweight was significantly higher (G Test; p